2015
DOI: 10.3390/en8053529
|View full text |Cite
|
Sign up to set email alerts
|

China’s Low-Carbon Scenario Analysis of CO2 Mitigation Measures towards 2050 Using a Hybrid AIM/CGE Model

Abstract: China's emissions continue to rise rapidly in line with its mounting energy consumption, which puts considerable pressure on China to meet its emission reduction commitments. This paper assesses the impacts of CO2 mitigation measures in China during the period from 2010 to 2050 by using a computable general equilibrium method, called AIM/CGE. Results show that renewable energy makes a critical difference in abating emissions during the period from 2010 to 2020. The scenarios with emission trading would drive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Computable, or applied, general equilibrium models (CGE) are simulations that combine the concept of market equilibrium with economic data, to numerically solve for the levels of supply, demand, and prices that support equilibrium across a set of markets. The empirical basis of CGE models is the interregional social accounting matrix (SAM), which records the revenues and expenses of all agents in the economy, classified as businesses, factors of production, households, government and the rest of the world (or the country), and provides the input–output coefficients of an economy . In this study, two main data sources feed the CGE model with balanced input–output coefficients: the interregional SAM for the baseline year of 2009, which describes the current sectors of the economy, and economic modeling of the biobased processes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computable, or applied, general equilibrium models (CGE) are simulations that combine the concept of market equilibrium with economic data, to numerically solve for the levels of supply, demand, and prices that support equilibrium across a set of markets. The empirical basis of CGE models is the interregional social accounting matrix (SAM), which records the revenues and expenses of all agents in the economy, classified as businesses, factors of production, households, government and the rest of the world (or the country), and provides the input–output coefficients of an economy . In this study, two main data sources feed the CGE model with balanced input–output coefficients: the interregional SAM for the baseline year of 2009, which describes the current sectors of the economy, and economic modeling of the biobased processes.…”
Section: Methodsmentioning
confidence: 99%
“…To satisfy the objectives proposed by the project, especially its interest in economy-wide changes in feedstock (from fossil to biobased), computable general equilibrium modeling (CGE) was chosen as the basic methodology, integrated with an economic input-output life cycle analysis (EIO-LCA). The use of CGE models and EIO-LCA's to analyze the energy-environment nexus has continuously grown and has many examples to offer, mainly focusing on carbon emissions, and carbon price, [9][10][11][12] emissions reductions and costs, 13,14 and, most important, land use and land-use change. For land-use change, an important publication dealing with deforestation and emissions 15 found that food output can increase without land supply expansion.…”
Section: Introductionmentioning
confidence: 99%
“…However, carbon tax levied in China has not really been implemented, and the tax rate is still no basis to determine the level of carbon tax to be imposed. In this regard, referring to the international carbon tax precedent, Li et al [37] whose research introduces carbon tax into China, Meng and Pham [38] whose research introduces carbon tax into the tourism sector in Australia, and Meng [39] whose research focuses on the impact of carbon tax on electricity sector, this article sets up six different scenarios to impose a carbon tax on agriculture-related sectors. Among them, according to the international general experience, the carbon tax should be set gradually in accordance with the low to high, and it is not reasonable to set the carbon tax too high, otherwise the impact on the macroeconomy will be more significant.…”
Section: Scenarios Designmentioning
confidence: 99%
“…The ETS modelling in the CGE model is usually handled by implementing an endogenous carbon tax or treating allowance as a special input factor [21][22][23][24][28][29][30][42][43][44][45][46]. Although the impacts of implementing an ETS or an endogenous carbon tax on economies are the same theoretically, emissions trading is a decision optimization process for each trader under the principle of cost minimization.…”
Section: Modelling Approach For Etsmentioning
confidence: 99%